TRANSFORMASI SASTRA ANAK DARI MEDIA CETAK KE DIGITAL: TANTANGAN DAN PELUANG DALAM LITERASI - Rubiah; Nurul Maulida; Anggi Nadilla; Nurul Nahwa Fadillah Nasution; Salsabillah Rahmadani; Vera Nika Br Tarigan; Sofia Handayani Harefa; Dewi Sartika Panggabean (STKIP Subang, 2026)
The Society Era 5.0 brought a shift in the medium of children's literature from static physical books to interactive digital platforms. This research aims to map the transformation of children's literary media and analyze its impact on the quality of literacy and the internalization of moral values. Using a descriptive qualitative method with a library research approach, data was collected through a literature review related to conventional and digital learning media. The results show that digital transformation offers opportunities in the form of participatory literacy and immersive multisensory experiences through audio-visual media and interactive platforms. However, cognitive challenges arise in the form of decreased deep reading skills due to skimming behavior and excessive cognitive load from multimedia features. The proposed optimization strategies include the application of dialogic reading, moral dilemma-based content curation, and the provision of cognitive scaffolding. In conclusion, the integration of technology in children's literature requires a balance between feature innovation and pedagogical depth to ensure that moral messages remain effectively internalized.